2023
DOI: 10.2147/idr.s432743
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of ß-Lactamase Genes Among Multidrug-Resistant and Extended-Spectrum ß-Lactamase-Producing Diarrheagenic Escherichia coli from Under-Five Children in Ethiopia

Tizazu Zenebe,
Tadesse Eguale,
Zelalem Desalegn
et al.

Abstract: Escherichia coli strains that produce extended-spectrum ß-lactamase (ESBL) and carbapenemase are among the major threats to global health. The objective of the present study was to determine the distribution of ß-lactamase genes among multidrugresistant (MDR) and ESBL-producing Diarrheagenic E. coli (DEC) pathotypes isolated from under-five children in Ethiopia. Patients and Methods:A cross-sectional study was conducted in Addis Ababa and Debre Berhan, Ethiopia. It was a health-facilitybased study and conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 70 publications
0
0
1
Order By: Relevance
“…These higher rates of the bla CTX-M-15 gene may be associated with incompatibility group FII conjugative plasmids which carry this gene and play a great role in the spread and acquisition of resistance genes in E. coli [48]. In contrast to the present study, bla TEM was found to be the predominant β-lactamase gene in a study with children under five years of age in Ethiopia [49] and in diarrheic patients in Ghana [50]. Several variants of the bla CTX-M and bla TEM genes have been identified on both plasmids and chromosomes [9,51].…”
Section: Mdr and Esbl-producing E Coli Among Studied Isolatescontrasting
confidence: 99%
“…These higher rates of the bla CTX-M-15 gene may be associated with incompatibility group FII conjugative plasmids which carry this gene and play a great role in the spread and acquisition of resistance genes in E. coli [48]. In contrast to the present study, bla TEM was found to be the predominant β-lactamase gene in a study with children under five years of age in Ethiopia [49] and in diarrheic patients in Ghana [50]. Several variants of the bla CTX-M and bla TEM genes have been identified on both plasmids and chromosomes [9,51].…”
Section: Mdr and Esbl-producing E Coli Among Studied Isolatescontrasting
confidence: 99%